ANALISIS PENGARUH HARGA, BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA DEALER HONDA JAYA TERANG 1 SITUBONDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Syafitri, Riezky Amalia Nur; Hamdun, Edy Kusnadi; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
This study aims to examine the influence of Price, Brand Image and service quality on consumer satisfaction. This research is classified as causality research. The population in this study is consumers of Honda Jaya Terang I Situbondo Dealers. Sampling in the study used purposive sampling. Data analysis and testing of research hypotheses using Smart PLS (Partial Least Square) analysis. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Price has a positive but not significant effect on Buying Interest, Brand Image has a positive but not significant effect on Buying Interest, Service Quality has a significant positive effect on Buying Interest, Price has a significant positive effect on Consumer Satisfaction, Brand Image has a positive but not significant effect on Consumer Satisfaction, Service Quality has a significant positive effect on Consumer Satisfaction, Buying Interest has a positive but not significant effect on Consumer Satisfaction. The results of the hypothesis test did not directly show that the Price variable had a negative but significant effect on Consumer Satisfaction through Buying Interest, Brand Image had a negative but not significant effect on Consumer Satisfaction through Buying Interest, Service Quality had a negative but not significant effect on Consumer Satisfaction through Buying Interest.